12/15‐Lipoxygenase deficiency reduces densities of mesenchymal stem cells in the dermis of wounded and unwounded skin. (1st July 2014) - Hong, S.; Alapure, B.V.; Lu, Y.; Tian, H.; Wang, Q.
Summary: Background: Mesenchymal stem cells (MSCs) promote skin healing. 12/15‐Lipoxgenase (LOX) is crucial in producing specific lipid mediators in wounded skin. The consequences of 12/15‐LOX deficiency in MSC densities in skin are unknown. Objectives: To determine the effect of 12/15‐LOX deficiency in MSC densities in wounded and unwounded dermis. Methods: Full‐thickness skin incisional wounds were made to 12/15‐LOX‐deficient (12/15‐LOX −/− ) and wild‐type (WT) C57BL/6 mice. Wounded skin was collected at 3, 8, or 14 days postwounding (dpw). MSCs were analysed in skin sections using histology. 12 S ‐ or 15 S ‐hydroxy‐eicosatetraenoic acid (HETE) was analysed using a reversed‐phase Chiral liquid chromatography–ultraviolet–tandem mass spectrometer. Results: There were more stem cell antigen (Sca)1 + CD29 + MSCs (cells/field) at 3, 8, and 14 dpw, more Sca1 + CD106 + MSCs at 3 and 14 dpw in the wounded dermis, more MSCs in unwounded dermis of WT mice compared with 12/15‐LOX −/− mice, and more MSCs in the wounded dermis than in the unwounded dermis. For 12/15‐LOX −/− dermis, Sca1 + CD106 + MSCs peaked and Sca1 + CD29 + MSCs reached a flat level at 8 dpw. However, for the WT dermis, MSCs increased from 8 to 14 dpw. There were more Sca1 + CD106 + MSCs than Sca1 + CD29 + MSCs in the 12/15‐LOX −/− wounded dermis at 8 dpw. However, there were more Sca1 + CD29 + MSCs in the 12/15‐LOX −/− than Sca1 + CD106 + MSCs in the WT wounded dermis at 3 dpw, and Sca1 + CD106 + MSCs and Sca1 + CD29 + MSCs were at comparable levels in other conditions. 12/15‐LOX deficiency suppressed levels of 12/15‐LOX protein and their products, 12 S ‐HETE and 15 S ‐HETE, in wounds. Conclusions: 12/15‐LOX deficiency reduces MSC densities in the dermis, which correlates with the suppressed 12/15‐LOX pathways in wounded and unwounded skin.